Talent Management – Recruiting, Evaluating and Retention of highly skilled employees: How should a Talent Management System (TMS) be configurated for Fraport AG and what are the main aspects to consider when implementing a TMS? - Mueller, Benjamin (2012)
In times of globalization and an ever increasing and accelerating worldwide economy, the success of an organisation depends heavily on one competitive advantage, which cannot be imitated, like physical or financial resources: the Human Factor/ the people within an organization. Products and services can be easily imitated, but the knowledge, the experience and the power of innovation of qualified and motivated employees are unique (Knowledge Infusion, 2006).